RESPON PERTUMBUHAN DAN HASIL TANAMAN EDAMAME (Glycine max (L.) Merr.) PADA BERBAGAI DOSIS PUPUK NPK DAN KASGOT BERBEDA - Ardiansyah, Mustofa; Pamungkas, Djoko Heru; Setiawati, Evi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine the growth response and yield of edamame soybean plantswith various doses of NPK Phonska fertilizer and different casgot which has been carriedout from October to December 2023, located in the